Perlindungan Hukum Obat-Obatan Tradisional dalam Perspektif Hukum Kesehatan dan Hukum Kekayaan Intelektual di Indonesia - Susi Susanti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Developments in the realm of health law develop in line with advances in health science. Currently, health law has become a very important element in dealing with various legal problems and issues in the health sector. On the other hand, with the development of increasingly sophisticated technology, the issue of traditional medicine has received less attention. However, in the context of efforts to fulfill the right to health in Indonesia, traditional medicine should be an alternative that is important to pay attention to. This is supported by Indonesia's natural conditions which have rich biodiversity, including various plant species that have the potential to be used as raw materials for traditional medicine. Thus, legal protection of traditional medicines from the perspective of health law and intellectual property law becomes very important. The research method used in this research is a normative research method which is conceptualized in legislation or conceptualized as norms or rules that serve as the basis for human behavior. The aim of this research is to analyze the legal protection of traditional medicines from the perspective of health law and intellectual property law in Indonesia. The results of this research concluded that related to traditional medicine, Law no. 17 of 2023 does not explicitly mention it as a traditional medicine. However, the definition of traditional medicine is equated with the term "Natural Medicine." In Article 321 paragraph (1), natural medicines are divided into several categories, including herbal medicines, standardized herbal medicines, phytopharmaca, and other natural medicines. Legal protection for traditional medicines or natural medicines is regulated in Articles 324-325 of Law no. 17 of 2023 concerning Health. On the other hand, in the context of Intellectual Property Rights (IPR), legal protection for traditional medicines is included in the patent system, as regulated in Article 26 of Law Number 13 of 2016 concerning Patents.